Beban Tas Siswa di Sekolah Dasar Saraswati 5 Denpasar - Harkitasari, Saktivi; Dewi Manuaba, Ida Ayu Laxmi Ananda; Primayanti, I Dewa Ayu Inten Dwi; Purnamasidhi, Cokorda Agung Wahyu (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2020)
The use of school bags without ergonomics design, miscarriage school bag, excessive bag load and carrying bags with long duration could be risk of disrupting the musculoskeletal system. The aim of this research is to know the frequency of bag load category of elementary students at SD Saraswati 5 Denpasar according to class, age, gender and weight of respondent. This research method was a descriptive cross-sectional study conducted at SD Saraswati 5 Denpasar. The sample in this study was selected by systematic random sampling. There were 86 respondents who carried load of bag of medium category amounted to 40 (46.5%) student, heavy bag category tend to carried by grade 3 student amounted to 12 (54.5%), male and female students carried the same bag load that is the moderate category 40 (46.5%) and the group with the mildest weight among other groups tend to carried heavy bag category amounted to 16 (55.2%). The conclusion is Students of Elementary School Saraswati 5 Denpasar more often carry the bag burden of the medium category. More heavy bag load categories are carried by students aged 7 years - 9 years. Groups of students with the lightest weight tend to carry heavy bag loads.